Innovative Strategies for Islamic Religious Education: Pesantren Day for Life Skill Development - Abdul Kholid Achmad; Noor Amiruddin; Hasan Basri (STAI Hubbulwathan Duri, 2025)
Life skills education is essential in shaping students’ character, confirming their roles as servants of God and stewards (khalifah) on earth. Embedding life skills into formal school curricula is necessary to nurture holistic human development grounded in Islamic values. This qualitative study, utilizing a phenomenological approach, was conducted at MI Unggul Sabilillah to explore the implementation of life skills education and identify supporting and inhibiting factors. Data were gathered through interviews, observations, and documentation to gain a comprehensive understanding of the phenomenon. The findings indicate that life skills education at MI Unggul Sabilillah is integrated through the innovative Pesantren Day program. This initiative includes structured, systematic activities aimed at developing student independence. These activities cultivate essential life competencies such as decision-making, interpersonal communication, self-awareness, mutual respect, discipline, self-regulation, confidence, and active participation. Students also demonstrate the ability to articulate ideas, think critically, understand religious teachings deeply, and exhibit leadership qualities. The consistent implementation of these programs is driven by the vision and philosophy of the madrasah's founders. Teacher expertise and commitment further enhance the effectiveness of life skills training. Continuous evaluation ensures that the programs remain effective and aligned with the school’s educational goals.